Eksistensi Pura Tanah Lot Dalam Perkembangan Pariwisata Budaya Di Kabupaten Tabanan - I Made Gami Sandi Untara; Wayan Supada (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The existence of temples in Bali is not immune from the influence of globalization. The temple, which was originally only a place of worship of the Gods for Hindus, began to change towards tourism so that it became a tourism destination. The existence of Tanah Lot Temple in Beraban Tabanan Village is also inseparable from the impact of cultural tourism that is developing in Bali. Tanah Temple is a natural and cultural tourist attraction because Lot has beautiful views of the sea, cliffs and waves, natural panoramas at sunset, religious activities that attract tourists, and is equipped with frequent interesting cultural festivals and Tanah Lot Temple has a very high history of cultural heritage because of the event or ceremony that takes place twice a year contributing to the attraction of tourists to see religious and cultural processions in Bali. This type of research is qualitative research using data collection methods, namely observation, interviews, literature study, and documentation. After the data collected will be analyzed using qualitative descriptive techniques. Keywords: Tanah Lot Temple, Cultural Tourism,